Mujmal and Mubayyan in Islamic Jurisprudence: Classical Foundations and Contemporary Applications - Ronaldi; Zulpandri; Refinal; Yondrizal; Ismaiza Busti; Alaa Alkhateeb (Solo International Collaboration and Publication of Social Sciences and Humanities, 2025)
Objective: To analyze the concept of mujmal and mubayyan in Ushul Fiqh and examine their implications for the process of legal istinbath and contemporary fatwa, emphasizing the importance of the bayan method in explaining the ambiguous meaning of the wording. Theoretical framework: This study uses the theoretical framework of Ushul al-Fiqh, especially the theory of the classification of shari'i words based on the clarity of meaning (mujmal and mubayyan) and the bayan method according to Imam al-Ghazali (al-Mustashfa), al-Amidi (al-Ihkam), as well as the approach of maqāṣid al-sharī'ah in the contextualization of law. Literature review: The mujmal word is understood as a word that requires additional explanation, while the mubayyan word has a clear meaning. Scholars such as al-Ghazali, al-Amidi, and Wahbah az-Zuhaili have discussed the forms of bayan and their functions in the legal istinbath. This study complements previous research by linking the concept to the context of contemporary fatwas. Methods: This research uses a qualitative method with a library research approach. Primary data sources are the classic books of ushul fiqh, while secondary data are obtained from contemporary literature, journal articles, and fiqh encyclopedias. The analysis is carried out through a descriptive-analytical approach with a focus on the structure of pronunciation and its relevance to modern legal problems. Results:  The pronunciation of mujmal and mubayyan has direct implications for the validity of the law. The mujmal recitation requires an explanation (bayan) before it is used as a legal basis, while the mubayyan recitation can be directly used as an argument. In the context of contemporary fatwas, the identification of the nature of the pronunciation is key in determining the ijtihad method and the maqashid approach. The Mufti is required to master the theory of lafazh as well as social reality so that the fatwa produced remains valid and contextual. Implications: Understanding the fazh of mujmal and mubayyan is important to strengthen the ushul fiqh curriculum and improve the accuracy of ijtihad and fatwa in dealing with modern legal issues. Novelty: This study integrates the theory of lafazh with the context of contemporary fatwas through the approach of maqāṣid al-sharī'ah, going beyond previous normative studies that tended to be theoretical.